ANALISIS BIOMEKANIKA GERAKAN SERVIS BAWAH BOLA VOLI SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN JASMANI - Ahmad Mursyidin; Muhammad Iksar; Riska Jaya Jaya; Supirman Rais; Muhammad Haerul (STKIP Subang, 2026)
This study aims to analyze the biomechanics of the volleyball underhand serve movement as a physical education learning medium. The underhand serve is a fundamental technique in volleyball that requires proper understanding of biomechanical principles to be taught effectively to students. This research used a qualitative descriptive method with a literature study approach, reviewing 15 relevant scientific articles and journals published between 2020 and 2025. The biomechanical analysis focused on joint movements, muscle activation patterns, angular velocity, and force applied during the underhand serve phases: preparation, execution, and follow-through. The results indicate that the underhand serve involves the coordination of multiple joints, particularly the shoulder, elbow, and wrist, with an optimal swing angle of 45–60 degrees to maximize ball trajectory consistency. Muscle activation analysis shows the anterior deltoid, pectoralis major, and triceps brachii are primary movers during the striking phase. The application of biomechanical principles in physical education learning provides a systematic framework for teachers to correct common technical errors, improve student motor learning efficiency, and reduce injury risk. This study concludes that biomechanical-based teaching approaches for the volleyball underhand serve significantly enhance the quality of physical education learning outcomes when properly integrated into lesson planning.